Effect of a thermal treatment on thermoplastic polyurethane– metal hybrids. (November 2018) - Puentes-Parodi, Alejandro; Gedan-Smolka, Michaela; Leuteritz, Andreas; Gehde, Michael; Kuehnert, Ines
The effect of a thermal treatment, i.e. annealing, on the adhesion of a thermoplastic polyurethane overmolded on a precoated steel substrate was evaluated. The hybrid part was subjected to three different annealing temperatures after the overmolding process. Adhesion of the thermoplastic elastomer was achieved by using an in-house-developed, two-step curable organic powder coating, which was selectively crosslinked to a polyallophanate state. The powder material was applied to the steel substrate by electrostatic charging followed by molecular crosslinking in an oven. The influence of the metal surface pretreatment was also evaluated regarding adhesion. The effects of the postthermal treatment were assessed through mechanical peel test, differential scanning calorimetry, atomic force microscopy, and scanning electron microscopy. Interesting results were obtained regarding strong adhesion between the precoated metal sheets and thermoplastic polyurethane after injection molding, especially in hybrids that were annealed at higher temperatures with the in-house adhesive coating.